Professional identities and the psycho-social contract - Costa, João Fontes da (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
This qualitative study combines extensive readings and fifty (50) in-depth interviews with pharmacists; the results indicate an important dynamics between the social and psycho-cognitive levels in professional identity narratives becoming salient upon the appraisal of the psychological contract and determining both attitudinal and behavioural related outcomes. We provide a theoretical model that incorporates professional identity in the employment relationship as an important determinant of the perceived delivery of the psychological contract, mediated by a social contractualization dimension with a regulative or normative character. Employment relationships are developed from macro-social levels and social contract perceptions define beliefs concerning the preferred or ideal terms of contract (Edwards & Karau, 2007; Rousseau, 1995). Professional norms and status related aspects are an upper individual and extra organizational conception that does not enter directly in many previous theoretical approaches. They convey an identity and identification forum with direct, however implicit, impacts in the perception of the delivery of the psychological contract. Social contractualization of a profession shapes individual knowledge or beliefs about the social matrix in which employment relationships are built. Employees experiencing incongruence between their social contract beliefs and psychological contract perceptions are more likely to consider a poor delivery on the psychological contract.